Phenotyping of recombinant inbred lines for early blight resistance in tomato - S.M. YADAV; MAJOR SINGH, LALIT RAMTEKE, VINEETA SINGH*, (Indian Phytopathology, 2013)
Tomato is one of the most remunerable and widely grown vegetables in the world. Early blight (Alternaria solani) is an important disease causing severe damage in tomato. Growing resistant varieties is the only effective, feasible technique for early blight management. More recent genetic studies on early blight resistance have been directed to the mapping and characterization of quantitative trait loci determining the resistance with the aid of molecular marker maps. A trial was conducted during rabi season, 2010-2011 to study phenotyping of recombinant inbred lines that have been developed for resistance against early blight of tomato caused by Alternaria solani. 179 recombinant inbred lines inoculated with 12 days old culture of Alternaria solani and disease severity was scored on a five-point scale. The frequency distribution curve of Area Under Disease Progress Curve predicted presence of major Quantitative Trait Loci.